2004
DOI: 10.1021/ja043688e
|View full text |Cite
|
Sign up to set email alerts
|

Peroxotungstate Immobilized on Ionic Liquid-Modified Silica as a Heterogeneous Epoxidation Catalyst with Hydrogen Peroxide

Abstract: Peroxotungstate immobilized on ionic liquid-modified SiO2 is capable of heterogeneously epoxidizing a wide range of olefins with the maintenance of the catalytic activity of homogeneous analogue. The epoxidation was immediately stopped by the removal of the catalyst, and no tungsten species could be found in the filtrate after the removal of the catalyst. These results can rule out any contribution to the observed catalysis from the tungsten species that leached into the reaction solution, and the observed cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
155
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(155 citation statements)
references
References 35 publications
0
155
0
Order By: Relevance
“…Based on the above observations, various groups reported their efforts to design POM-based heterogeneous catalytic systems for the promotion of specific reactions. For example, Mizuno et al reported the preparation, efficiency and stability of a peroxotungstate immobilized on ionic liquid-modified SiO 2 heterogeneous catalyst for the epoxidation of a wide range of olefins [32]. In another case, Inumaru et al demonstrated the efficiency of a POM-SiO 2 heterogeneous catalyst where H 3 PW 12 O 40 species immobilized the channels of mesoporous silica decorated with hydrophobic alkyl groups.…”
Section: Pom-ldh Composite Materialsmentioning
confidence: 99%
“…Based on the above observations, various groups reported their efforts to design POM-based heterogeneous catalytic systems for the promotion of specific reactions. For example, Mizuno et al reported the preparation, efficiency and stability of a peroxotungstate immobilized on ionic liquid-modified SiO 2 heterogeneous catalyst for the epoxidation of a wide range of olefins [32]. In another case, Inumaru et al demonstrated the efficiency of a POM-SiO 2 heterogeneous catalyst where H 3 PW 12 O 40 species immobilized the channels of mesoporous silica decorated with hydrophobic alkyl groups.…”
Section: Pom-ldh Composite Materialsmentioning
confidence: 99%
“…[25][26][27] The FT-IR spectrum and XRD pattern of Mg3Al-NO3 as well as the FT-IR spectrum, 1 H CP/MAS NMR and 13 C CP/MAS NMR spectra of IL-PF6 are shown in supporting information.…”
Section: Synthesis Of Mg3al-il-euw10mentioning
confidence: 99%
“…The choice of the support depends generally on the desired reaction and could be organic as resin or inorganic as silica. Yamaguchi et al [58] reported a few years ago the immobilization of the peroxotungstate catalyst on dihydroimidazolium-based ionic liquid modified SiO 2 . The immobilized catalyst presents the same activity in the liquid phase epoxidation of various olefins by H 2 O 2 as its homogeneous analogue.…”
Section: Ionic Liquid: Polyoxometalates Hybridsmentioning
confidence: 99%